ANALISA FAKTOR KEHILANGAN ENERGI PADA DISTRIBUSI PIPA DARI BOOSTER KERTAPATI SAMPAI KAWASAN PASAR - Oemiati, Nurnilam; Kimi, Sudirman; Anggraini, Rani (Universitas Muhammadiyah Palembang, 2021)
To meet the needs of clean water in the Sungki Simpang Market Area, the distribution of clean water plays an important role and is very much needed by local residents. There are still many obstacles that result in a lack of water supply, so that people rely heavily on PDAM Tirta Musi Booster Kertapati to meet their clean water needs.In this study, the authors analyzed the energy loss factors in the distribution network of clean water pipes from Booster Kertapati to Sungki Simpang Market Area, factors that affect energy loss in the pipe distribution network include flow rate, flow velocity, pipe bend angle, pipe friction, and change in pipe cross- section.The results of the calculation show that the largest total energy loss is in the I-J pipe segment of 71.47446 m, the Ø0,1016 m or Ø4 inch pipe with a speed of 4.35800 m/s and the smallest total energy loss is in the C'-C pipe section of 0.10979 m , the Ø0,1016 m or Ø4 inch pipe at 1.38004 m/s. So it can be concluded that not only the number of turns, changes in the cross-section and length of the pipe that affect the energy loss factor, the flow velocity is also a factor in the energy loss.Keywords: Energy Loss Factor, Analysis Result.